Doom patrol. The complete second season [videorecording (DVD)] - Guerrero, Diane, 1986-; Bowlby, April, 1980-; Wade, Joivan, 1993-; Bomer, Matthew, 1977-; Fraser, Brendan, 1968-; Dalton, Timothy, 1944- (Warner Bros. Home Entertainment, 2021)
DC's strangest group of heroes is back again to save the world - that is, if they can find a way to grow up.